PERCEIVED QUALITY OF RURAL TOURISM ACCOMMODATION SERVICES BY PROSPECTIVE CUSTOMERS - Dembovska, Iveta; Silicka, Inese; Litavniece, Lienite (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Rural tourism and corresponding activities generate new jobs, providing employment for people in rural areas, create a cooperation mechanism between different rural entrepreneurs, attract tourists, and thus contribute to both well-being of local population and the regional development in general. Rural tourism is attractive from an economic perspective, as it provides the opportunity to boost and diversify rural economies in remote areas. The paper is a part of the RTA scientific grant "Tourism Products Evaluation of the Rezekne Municipality (Quality Audit)". The aim of the research is to study rural tourism accommodation services in Rezekne municipality and to carry out their evaluation based on experts’ (potential customers’) perception of quality. The methods applied in the research: logical and constructive, synthesis and analysis, an empirical survey. However, the rural tourism accommodation establishments in Rezekne municipality in general are characterized by the keywords "responsiveness" and "hospitality" as well as by the well-ordered environment around the houses. The rural housings have to evaluate the current and future demand and precisely define the potential market segments to create an offer in accordance with it.